Uncovering the microscopic mechanism of incorporating Mn2+ ions into CsPbCl3 crystal lattice. Issue 36 (2nd September 2019) - Xia, Jienan; Lu, Song; Lei, Lei; Hua, Youjie; Xu, Shiqing
Abstract : Based on a four-precursor synthetic strategy and DFT calculation, we verify that excessive chloride ion concentration benefits the formation of bond [Pb⋯Cl] vacancy pair as well as the subsequent incorporation of [Mn⋯Cl] ion pair. Abstract : Cation doping strategy has been extensively employed to enhance the charge carrier mobility and improve the stability of halide perovskites; however, the fundamental understanding of the inherent doping mechanism is still a challenge. Herein, based on a unique four-precursor synthetic strategy and density functional theory (DFT) calculation results, we verify that excessive chloride ion concentration benefits the formation of the bond [Pb⋯Cl] vacancy pair as well as the subsequent incorporation of the [Mn⋯Cl] ion pair synchronously. As a result, high Cl − ion concentration greatly promotes the incorporation of the Mn 2+ ions into the CsPbCl3 crystal lattice. The particle size reduction of the CsPbCl3 perovskite with the incorporation of the Mn 2+ ions is attributed to the increased surface electron charge density, which inhibits the diffusion of the negatively charged Cl − ions to the nuclei surface. These deep insights into the inherent Mn 2+ doping mechanism could guide the realization of novel ion-doped perovskites with new optoelectronic performances.